Diagnosis and Management of Superior Canal Dehiscence Syndrome - Rio Mulya Riharta; Rossy Rosalinda; Muhammad Dilga Caesario (Fakultas Kedokteran Universitas Andalas, 2026)
Diagnosis and Management of Superior Canal Dehiscence Syndrome Background: Superior Canal Dehiscence Syndrome (SCDS) is a vestibulocochlear disorder caused by a bony defect in the superior semicircular canal, creating a pathological third window in the labyrinth. This condition produces a variety of vestibular and auditory manifestations that significantly impair quality of life. Objective: To know and understand the diagnosis and management of superior canal dehiscence syndrome. Literature Review: The etiology of SCDS may be congenital or acquired. The primary pathophysiology relates to the third window mechanism that disrupts acoustic energy transmission and generates abnormal pressure pathways within the labyrinth. Characteristic vestibular symptoms include the Tullio phenomenon, Hennebert sign, oscillopsia, and disequilibrium, while cochlear symptoms encompass autophony, bone-conduction hyperacusis, pulsatile tinnitus, and low-frequency conductive hearing loss. Diagnosis is established based on the Barany Society triadic criteria: clinical symptoms, neurophysiological testing (VEMP, audiometry), and High-Resolution Computed Tomography (HRCT) imaging with multiplanar reconstruction. Conservative management is indicated for mild cases, while surgical treatment, via the middle cranial fossa (MCF) or transmastoid (TM) approach, is recommended for patients with severe, debilitating symptoms. Conclusion: Superior canal dehiscence syndrome (SCDS) is a third mobile window disorder caused by a bony defect of the superior semicircular canal, resulting in vestibular and auditory symptoms. Diagnosis is established through an integrative approach based on the Bárány Society criteria, incorporating clinical correlation, VEMP and/or audiometry, and high-resolution CT imaging. Management is stepwise, with surgical intervention (plugging or resurfacing) serving as the definitive treatment in severely symptomatic cases to eliminate the pathological pathway and improve clinical outcomes.